2006
DOI: 10.1177/1043659605281973
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Asylum: Implications for Nursing and Health Care Delivery for Afghan Refugees in Australia

Abstract: Descriptions of the refugee experience, together with an analysis of access, use, and appropriateness of mental and physical health services as perceived by members of the Afghan immigrant or refugee community living in New South Wales (NSW), Australia, are reported in this article. Using focus groups and semistructured interviews in a variety of settings, the study included 13 key informants and 25 general informants, together with health care agencies providing services to the Afghans and organizations provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 16 publications
3
73
0
Order By: Relevance
“…Ten studies were combined as they essentially used the same sample in separate publications. These combinations were as follows: one mixed-method [81] and one quantitative (validation) study [101] (the other mixed-method study [80] was later eliminated as findings were reported for only a subset (one-third) of the entire sample); four qualitative studies [3, 85, 87, 88]; and four quantitative studies [90, 91, 98, 99]. This subsequently resulted in a total sample size ( n ) of 17 studies (one mixed-method, seven qualitative, nine quantitative).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were combined as they essentially used the same sample in separate publications. These combinations were as follows: one mixed-method [81] and one quantitative (validation) study [101] (the other mixed-method study [80] was later eliminated as findings were reported for only a subset (one-third) of the entire sample); four qualitative studies [3, 85, 87, 88]; and four quantitative studies [90, 91, 98, 99]. This subsequently resulted in a total sample size ( n ) of 17 studies (one mixed-method, seven qualitative, nine quantitative).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] In our study, overall proficiency and use of English in the home increased with a longer period of residency in Australia. However, the ability to communicate effectively with health professionals is also influenced by other factors such as knowledge of the 'language of healthcare' and cultural perceptions of illness.…”
Section: Discussionmentioning
confidence: 95%
“…None of the nurses related the behaviour to the families' cultural characteristics. Omeri et al (2006) recommend empowering, improving interpreter services and promoting understanding of religious practices to improve the health of refugees entering Australia, which would be appropriate for nurses and multicultural families in other countries as well. The nurses perceive the Norwegian people as cool and emotionally non-expressive compared to culturally different families.…”
Section: Discussionmentioning
confidence: 99%